Crystal structures of human HMG-CoA synthase isoforms provide insights into inherited ketogenesis disorders and inhibitor design. - Shafqat, N; Turnbull, A; Zschocke, J; Oppermann, U; Yue, W (2010)
3-Hydroxy-3-methylglutaryl coenzyme A (CoA) synthase (HMGCS) catalyzes the condensation of acetyl-CoA and acetoacetyl-CoA into 3-hydroxy-3-methylglutaryl CoA. It is ubiquitous across the phylogenetic tree and is broadly classified into three classes. The prokaryotic isoform is essential in Gram-positive bacteria for isoprenoid synthesis via the mevalonate pathway. The eukaryotic cytosolic isoform also participates in the mevalonate pathway but its end product is cholesterol. Mammals also contain a mitochondrial isoform; its deficiency results in an inherited disorder of ketone body formation. Here, we report high-resolution crystal structures of the human cytosolic (hHMGCS1) and mitochondrial (hHMGCS2) isoforms in binary product complexes. Our data represent the first structures solved for human HMGCS and the mitochondrial isoform, allowing for the first time structural comparison among the three isoforms. This serves as a starting point for the development of isoform-specific inhibitors that have potential cholesterol-reducing and antibiotic applications. In addition, missense mutations that cause mitochondrial HMGCS deficiency have been mapped onto the hHMGCS2 structure to rationalize the structural basis for the disease pathology.